The use of endoscopic ultrasound in tandem with endoscopic retrograde cholangiopancreatography in the 2019 American Society for Gastrointestinal Endoscopy guideline for patients at high risk of choledocholithiasis can help to avoid diagnostic endoscopic retrograde cholangiopancreatography in individuals without ascending cholangitis - Apichet Sirinawasatien; Jiravit Chanchairungcharoen; Thanapon Yaowmaneerat; Jirat Jiratham‐opas; Kanokpoj Chanpiwat; Tanyaporn Chantarojanasiri; Siriboon Attasaranya; Kannikar Laohavichitra; Jerasak Wannaprasert; Thawee Ratanachu‐ek (DEN Open)
Abstract Objectives Choledocholithiasis is the leading cause of biliary pancreatitis and biliary sepsis. Endoscopic retrograde cholangiopancreatography (ERCP) is considered a minimally invasive treatment for choledocholithiasis. However, diagnostic ERCP should be avoided. We conducted a prospective trial in high‐risk choledocholithiasis patients based on the American Society for Gastrointestinal Endoscopy (ASGE) 2019 criteria to investigate the diagnostic accuracy of the current guideline. Methods This multicenter, prospective cohort study included 240 consecutive patients. The primary outcome was the performance of the criteria in predicting choledocholithiasis. The secondary outcome was a percentage reduction in diagnostic ERCP when endoscopic ultrasound was used in tandem with ERCP in individuals without ascending cholangitis. Results The overall criteria revealed a positive common bile duct (CBD) stone in 87.1% of patients. Regarding the diagnostic performance of each criterion, ascending cholangitis had a specificity of 67.7% and a positive predictive value (PPV) of 90.2%; total bilirubin >4 mg/dL and dilated CBD had a specificity of 74.2% and a PPV of 55.6%; and CBD stone on ultrasound/cross‐sectional imaging had a specificity of 58.1% and a PPV of 89.2%. Of the 138 patients without ascending cholangitis who met the other two high‐risk criteria and were sent for EUS first, 21 cases (15.2%) were able to avoid a diagnostic ERCP. Conclusions The current ASGE 2019 criteria yield acceptable choledocholithiasis diagnostic accuracy. Using endoscopic ultrasound to confirm CBD stones before ERCP can help almost half of patients with the specific condition of total bilirubin >4 mg/dL and dilated CBD to avoid diagnostic ERCP.